Enhancing Students' Morphology by Using Painting with Letters for Secondary Level - Daulay, Sholihatul Hamidah; Asmawati, Asmawati (ELITE JOURNAL, 2025)
This research aimed to enhance students' morphology by using painting with Letters strategy for the secondary level. A literature review has been done in this study; the present study employed George's (2008) model of library research. As the main argument, the present study adopted the concept of differentiated instruction from Tomlinson (1999, 2001, 2014), Tomlinson and Imbeau (2010), and Tomlinson and Moon (2013) to answer the present study's research questions, supported by other relevant sources. The data were collected from the students of secondary level related to the study. The results showed that the characteristics of students' paintings can stimulate the enhancing of students' morphology and have a profound impact on art. The development of their vocabularies has important implications for the secondary level and certainly for secondary learners who are on the budding edge of propelling themselves from the task of learning to read into the realm of reading to learn. The student's paintings at the secondary level can increase and also improve the creativity of their learning process in morphology.